Rheumatoid arthritis in real clinical practice: initiation of therapy with biological agents. Results of the «Computer Terminals of Self-Assessment for Patients with Rheumatic Diseases» («TERMINAL-II») project - V. N. Amirdzhanova; E. Yu. Pogozheva; A. E. Karateev; O. V. Antipova; I. B. Vinogradova; A. Yu. Kazankova; R. G. Mukhina; A. G. Vasilyev; O. B. Nesmeyanova; E. A. Bogdanova; R. R. Samigullina; A. A. Vasilenko; et al. (Современная ревматология)
Objective: to assess quality-of-life (QoL) dynamics in patients with rheumatoid arthritis (RA) when initiating therapy with biological agents (BAs) in real clinical practice.Patients and methods. The investigation enrolled patients with RA from the patient cohort participating in the TERMINAL-II multicenter Russian study, who newly initiated BA therapy. In the self-assessment terminal, the patient completed HAQ, EQ-5D, and RAPID-3 questionnaires. DAS28, SDAI, CDAI, and RAPID-3 were used to determine disease activity. The patient's functional status and QoL were assessed using the HAQ index and the EQ-5D questionnaire, respectively. The efficiency of the therapy was analyzed 6 months after the start of the study according to the standard procedures.Results and discussion. The investigation enrolled 156 RA patients: 79.6% females; mean age, 45.8±13.2 years; disease duration, 7.6±5.6 years. The patients had high RA activity (a mean DAS28 of 5.2±1.2, a mean SDAI of 39.5±16.4, a mean CDAI of 27.5±10.4, and a mean RAPID-3 of 15.1±3.6) and previous inefficacy of synthetic disease-modifying antirheumatic drugs (DMARDs) after at least 6 months of therapy. Only 1.2% of patients had a good functional status comparable to the population-based control (HAQ 40.5). 70% of patients needed to take non-steroidal anti-inflammatory drugs (NSAIDs). The first BA was chosen in accordance with the recommendations for administration of BAs and in terms of their availability in a specific region of the Russian Federation. The first prescribed BA was tumor necrosis factor-a (TNF-a) inhibitors in 112 (71.8%)patients, anti-B-cell therapy in 14 (9.0%), an interleukin-6 receptor inhibitor in 16 (10.3%), and a leukocyte costimulatory inhibitor in 14 (9.0%). Comparison of the patients receiving newly initiated therapy with TNF-a inhibitors and drugs with other mechanisms of action showed that the patients who had abatacept received higher doses of methotrexate (MTX), but lower doses of glucocorticoids (GCs) than those who were prescribed rituximab and tocilizumab. A statistically significant decrease in DAS28, SDAI, CDAI, and RAPID-3 scores was achieved after 6 months of therapy. Improvements of functional status and QoL in patients were also noted (p<0.0001). The patients continued to receive MTX. During the follow-up period, its dose remained almost unchanged: it averaged 15.7±3.8 and 15.7±3.7 mg/week at the beginning and the end of the study, respectively. Due to decreased inflammation, the dose of CS was reduced (on average, from 5.8±2.5 to 5.1±2.6 mg/day; p=0.02), the number of patients requiring NSAIDs declined (from 72.4 to 63.8%). DAS28, SDAI, and CDAI remission and low disease activity were achieved in 38.1, 16.5, and 20% of patients, respectively. The functional status improved in most patients with RA: 20, 50, and 70% improvements in HAQ were observed in 59.4, 46.9, and 28.7% of cases, respectively. QoL improvements were seen in two thirds of the patients: 30, 50, and 70% improvements in 58.3, 29.5, and in 23.7%. After 6-month follow-up, GC therapy was completely discontinued in 4.6% of patients; their dose was reduced in 5.3%, and 8.6% completely refused to take NSAIDs.Conclusion. Biologic therapy was shown to be effective in RA patients with an inadequate response to synthetic NSAIDs in real clinical practice. The patients preferred the subcutaneous injection of BAs. Biologic treatment in most patients was initiated with TNF-a inhibitors, mainly with adalimumab. Six-month therapy could reduce disease activity and improve functional status and health-related QoL in two thirds of severe patients.